Diagnosis and imaging of diaphragmatic eventration: A case report - Nasution, Ikhwanul Hakim; Soekardi, Adi; Mahatvavirya, Redo Widhio (Jurnal Prima Medika Sains, 2024)
Background: Diaphragmatic eventration is a rare disorder that is typically found by accident in asymptomatic patients with a raised hemidiaphragm on chest X-rays. Both acquired and developmental defects can cause diaphragmatic eventration. The imaging methods for diaphragmatic eventration are numerous. Chest radiography should be done when there is clinical suspicion; this can be further confirmed with a chest computed tomography (CT). Case presentation: We present a case of a 37 years old woman with a left sided diaphragm eventration presenting as dyspnea and epigastrical discomfort. The diagnosis was made with chest x-ray and then confirmed with a chest CT scans. Discussion: There are several modalities to choose in diaphragmatic imaging. Chest x-ray is the main imaging method for diagnosing diaphragm eventration, in rare cases, a eventration needs to be differentiated using CT or MRI. Other imaging methods such as fluoroscopy and ultrasonography may be used in some instances to assess diaphragm function. Conclusions: There are various methods available in the field of diaphragmatic imaging. Certain methods, like CT and plain chest radiographs, concentrate on the anatomic anomalies of the diaphragm that may indicate dysfunction. Some instruments, including fluoroscopy and ultrasonography, are more appropriate for functional imaging.